Why? - Tilly, Charles (Princeton University Press, 2006)
"Why? is a book about the explanations we give and how we give them - a look at the way the reasons we offer every day are dictated by, and help constitute, social relationships. Written in an easy-to-read style by distinguished social historian Charles Tilly, the book explores the manner in which people claim, establish, negotiate, repair, rework, or terminate relations with others through the reasons they give."--Jacket